Neoliberal White Corporate Saviourism in Public Education Outsourcing: A Critical Examination of Project 11 - Mayor, Christine; Janzen, Melanie; Sanni-Anibire, Hafizat (Journal of Contemporary Issues in Education, 2025)
Private and corporate interests continue to find new ways to penetrate public K-12 education in Canada, often through the outsourcing of services that are best provided by school-based professionals. In this article, we explore how neoliberal privatization intersects with the discourse of white corporate saviourism through philanthropic non-profit organizations that infiltrate schools under the guise of goodwill and benevolence. Using Project 11 (a mental health non-profit program largely funded by the organization who owns the Winnipeg Jets) as an example of this phenomenon, we illustrate how such organizations may embed themselves in under-resourced schools —made vulnerable by neoliberal reforms— while simultaneously reaping additional social and economic benefits for their involvement. We caution that while programs such as Project 11 may appear —or indeed be— well intentioned, we must maintain critical vigilance against the creeping of white corporate saviourism into our schools. These programs often personalize deeper structural issues, advance corporate interests, reinforce neoliberal ideologies, diminish the role of educators, and perpetuate whiteness and colonial legacies within public education. The presence of private actors within public schools must be scrutinized for the ways in which they may attempt to reshape education to benefit corporate agendas rather than the public good.